Consulting for the textile company Creditex S.A.A - Arbeiter, Charlotte (2020)
Creditex is one of the largest Peruvian textile companies listed on the Lima stock exchange. The main activity of the company is the manufacture of textile products, including ginning, spinning, weaving, dyeing, finishing and all activities related to the industrial processing of natural fibers of plant, animal and synthetic origin. Creditex is specialized in the development of complete clothing packages for major international brands such as Tommy Bahamas, Life is good, Island Company, and others. Creditex is facing a decline in its sales and an increase in its manufacturing and labor costs. One reason for the rapid decline in sales is seen in ineffective product development. Therefore, the research question of this thesis is as follows: Which product development for the Latin American and US market enables Creditex to achieve sustainable success? The methodology used is a single case study. Relevant literature was collected by means of a literature review and expert interviews. Following the literature review, four different possible solutions are presented, which are then systematically analyzed and ranked according to several assessment criteria. The company Creditex is shown one short and one long term solution. The proposed solution suggested to the company is to implement a new product line focusing on medical clothing and sports and leisurewear, taking into account the current demand for both products and the growing expectations of both markets.